IN VITRO ASSESSMENT OF ANTIOXIDANT AND ANTIBACTERIAL ACTIVITY OF GREEN SYNTHESIZED SILVER NANOPARTICLES FROM DIGITARIA RADICOSA LEAVES - T, Kalaiyarasu; N, Karthi; V, Sharmila Gowri; V, Manju (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Green metallic nanoparticles were creating a new era in the field of green nanotechnology and its applications. Methanolic leaf extract of rare, endemic medicinally important herb, Digitaria radicosa used for the synthesis of silver nanoparticles (SNPs). UV Visible spectrophotometric analysis confirmed the synthesis of green silver nanoparticles indicated by the peak observed at 442nm due to the excitation of surface plasmon resonance in the silver nanoparticles. FT-IR spectroscopic analysis showed the availability of functional groups which may involve in the silver nanoparticles synthesis. X-Ray Diffraction pattern illustrated the characteristic peaks of (111), (122), (231) facets of the centre crystalline and cubic face centred nature of silver nanoparticles. SEM analysis showed that synthesized green silver nanoparticles were of spherical in shape and size of around 90 nm. The free radical scavenging activity of silver nanoparticles were evaluated in vitro by using DPPH scavenging activity, metal chelating activity, reducing power assay and hydrogen peroxide scavenging assays. The antibacterial activity against food borne pathogens such as S. aureus and E .coli were determined by disc diffusion method. The results confirmed that these synthesized green silver nanoparticles identified to have significant in vitro antioxidant potential and good antibacterial activity. Keywords: Green Silver nanoparticles, SNPs, Digitaria radicosa leaf extract, UV Visible spectrophotometry, XRD, FT IR, SEM, in vitro antioxidant assays, antibacterial activity.